ADRIAN, Melanie. Religious Freedom at Risk. The EU, French Schools, and Why the Veil was Banned - Andrea Hrebičková (Časopis pro Právní Vědu a Praxi, 2019)
Switzerland: Springer International Publishing, 2016. ISBN 978-3-319-21445-0.